MITIGASI BENCANA BANJIR STRUKTURAL DAN NON-STRUKTURAL DI KABUPATEN BOLAANG MONGONDOW SELATAN - Urbanus, Ananda; Sela, Rieneke L. E.; Tungka, Aristotulus E (SPASIAL, 2021)
South Bolaang Mongondow Regency is one of several regencies in North Sulawesi province, where this area is often referred to by observers as a non-zom area or there is no precise season to predict. So that hydrometeorological disasters, especially floods, are very likely to occur if there is no prevention stage in disaster management. The flood incident that submerged almost all areas in the sub-district on July 24, 2020 proved that preparedness was needed in dealing with the flood disaster which caused 93 houses to be heavily damaged and 165 people evacuated (DIBI, 2020). The level of disaster risk looks at how the index of the hazard, vulnerability, and capacity of a disaster can be, so that the level of risk of a flood disaster can be known. In determining disaster risk, using the policy of the Regulation of the Head of the National Disaster Management Agency Number 2 of 2012 concerning General Guidelines for Disaster Risk Assessment. The results of the existing risk level will then be used as recommendations for later flood disaster mitigation, both structurally and non-structurally. The level of flood risk resulted in 3 villages with a high level of flood risk, 14 villages with a moderate level of flood risk, and 42 villages with a low level of flood risk. Disaster mitigation that adapts to the level of risk from disasters where villages with high flood risk are recommended to make plans for physical (structural) development in an effort to reduce the danger from flooding, then villages with moderate flood risk are recommended for additions or improvements regarding physical form ( structural) flood control that already exists or does not exist, and areas with low flood risk, it is recommended to improve the physical (structural) form of existing flood control, but not optimal in the implementation system.KEYWORDS : Mitigation, Flood Disaster, Structural, Non-Structural, Risk Level